Holy Harlots : Femininity, Sexuality, and Black Magic in Brazil - Hayes, Kelly E., 1968- (Book collections on Project MUSE., 2011)
This title examines the intersections of social marginality, morality, and magic in contemporary Brazil by analyzing the beliefs and religious practices related to the Afro-Brazilian spirit entity Pomba Gira.